Forming a Sakinah Family through Marriage Guidance for Brides-to-be during the Pandemic: Membentuk Keluarga Sakinah Melalui Bimbingan Pernikahan Bagi Calon Pengantin di Masa Pandemi - Azizah, Imroatul; Isroani, Farida (Indonesian Journal of Law and Economics Review, 2023)
The Covid-19 pandemic has increased the number of divorces that have occurred. Many couples choose to divorce because of economic, psychological, biological factors, domestic violence, differences in outlook on life, and so on. The Covid-19 pandemic has changed various aspects of life, especially in terms of the family economy. The implementation of marriage counseling is considered capable of reducing the high divorce rate during the pandemic, however, there are those who question its effectiveness. The use of descriptive methods and qualitative approaches in this study shows the fact that the implementation of marriage counseling in Tuban Regency Religious Affairs Office had a positive impact on the bride and groom. Data collection techniques in this study using interviews and observation. From the results of the research it is known that the implementation of marriage guidance which is carried out with the material of marriage, household, reproductive health and family is quite effective in reducing the high number of divorces during the Covid-19 pandemic.